The Effect of Adding Cornstarch to The Chemical Characteristics of Green Mussel Paste Flavor - Mila Ayu; Endang Dewi Masithah; Eka Saputra (Journal of Marine and Coastal Science, 2022)
Green mussels is one of Indonesia's fisheries commodities that has a high export value. The high export activity of shellfish products will have an impact on the environment due to shell waste produced. Utilization of shell shell waste is a solution to overcome environmental pollution and can be in the form of diversification of food products that can be used as raw materials for food flavorings. Making a food flavor or natural flavor requires an emulsifier. One ingredient that can be used as an emulsifier is cornstarch. The purpose of this study was to determine the effect of adding cornstarch to the chemical characteristics of the green mussel paste flavor. This study used a Completely Randomized Design (CRD) consisting of 5 treatments with cornstarch concentration of 0%, 2.5%, 5%, 7.5%, and 10% with 4 replications. Protein and fat content are the main components of making flavors. The main parameters used in this study are flavor paste with emulsifier having proximate levels (protein, water content, and fat content) and supporting parameters are yield, VRS levels, water solubility, and pH levels. The results of this study indicate that the addition of gelatin has a significant effect (P <0.05) on the chemical characteristics of protein, fat, water content, yield, water solubility, VRS, and pH. Pasta flavor with a concentration of 10% has good levels of protein, fat, water content, yield value, water solubility , and VRS.